(untitled) (SAARC Journal of Agriculture, 2024)
Diversified plant species in homestead areas play an important role to ensure the food and nutritional security of rural communities. An exploratory survey and field observation was carried out at Sadar upazila of Rangamati district in Bangladesh to identify the existing plant biodiversity in the homestead areas of six unions along with municipal area of Rangamati Sadar upazila. A total of 120 households were randomly selected for collecting data using face-to-face interviews from July to September 2020. A total of 163 plant species were identified at different homesteads of the study area. Among different categories of plant species, 13 (7.98%) timber, 32 (19.63%) fruits, 19 (11.66%) medicinal species, 31 (19.02%) different vegetable species, 56 (34.36%) different flowering and ornamental species, 08 (4.91%) spices and condiments and 04 (2.45%) other plant species were recorded. The front yard was dominated by most of the plant species whereas the kitchen side was dominated by vegetables. The highest diversity was found in vegetables (H’= 0.96) followed by medicinal plant and fruit species (H’= 0.83), timber, and flower and ornamental species (H’= 0.82). A moderate diversity was found at the back side (H’=0.69) followed by the boundary side (H’=0.68), front yard (H’=0.65) and, approach road (H’=0.60). The study concludes that homestead agroforestry is a unique area for maintaining both plant diversity and productivity which could be a good option to meet up the demand of food and nutrition of the people in hilly areas. SAARC J. Agric., 22(1): 203-221 (2024)